Physics based approaches for active rotor control technology - Sankar, L.N.; Prasad, J.V.R.; He, C. (My University, 2017)
A methodology for physics based reduced order modeling of next generation OBC concepts suitable for fast and real time simulations has been integrated with a computationally efficient framework for extraction of time-invariant linearized models suitable for handling qualities assessment and integrated flight and rotor control design and analyses. The accuracy of the developed reduced-order models has been evaluated through comparisons with high fidelity CFD predictions and available test data. The reduced order models have been integrated into the modular architecture of FLIGHTLAB simulation model for fast and real time demonstrations. New algorithms have been developed by exploiting the harmonic domain representation of rotor states for extraction of LTI models of coupled body-rotor dynamics suitable for various control design applications with IBC and OBC concepts and for handling qualities assessment. The extracted LTI models have been validated through comparisons with the nonlinear model predictions in time and frequency domains.